The structure and incidence of infection in the cysts in patients with autosom al dominant polycystic kidney disease on the waiting list of kidney transplantation - V. S. Daineko; A. N. Ananiev; E. S. Nevirovich; N. R. Naser; V. A. Manukovskiy; O. N. Reznik (Вестник трансплантологии и искусственных органов, 2018)
Aim. To investigate the structure and frequency of occurrence of the infection in the cysts of the kidneys in patients with end-stage renal disease (ESRD) due to autosomal dominant polycystic kidney disease (PKD).Materials and methods. For the first time the microbiological study of the biological materials obtained from the patients with PKD were performed. That  were the polycystic-altered kidneys removed in preparation of potential  recipients for kidney transplantation, which were made as a routine step. All  patients underwent surgical treatment in order to prepare for kidney  transplantation or according to clinical indications. Two groups of patients have  been distinguished: the 1st group – 7 (33.3%) patients with asymptomatic  course of disease, the 2nd group – 14 (76.7%) patients who had symptoms of infection of kidneys and urinary tract.Results. As a result of this work, the presence of latent and active infection in  18 (85.7%) patients, including 6 (85.7%) patients with asymptomatic polycystic course, was proved. At microbiological research the causative agent of infection was not revealed only at the 1st patient in the first group and in 2  patients in the second group. Infection of cysts of kidneys of 6 patients with asymptomatic course of PKD was proved only after research of their  contents taken intraoperatively. There is no correlation between the presence of  infection, symptoms and the size of polycystic kidneys. Multidrug resistant infection only sensitive to modern antibiotics ultrawide spectrum of  action was detected in 6 patients, including 2 patients with asymptomatic.Conclusion. Critically high actual infection of more than 80% of polycystic-altered kidneys has been established, which allows to consider them as a source  of chronic infection in the context of future transplantation. The presence of  latent, including multiresistant infection in cysts, worsens the prognosis of kidney transplantation in this category of patients without nephrectomy.